Interplay between pulsations and mass loss in the blue supergiant 55 Cygnus = HD 198 478 - Kraus, M. (2015)
Context. Blue supergiant stars are known to display photometric and spectroscopic variability that is suggested to be linked to stellar pulsations. Pulsational activity in massive stars strongly depends on the star's evolutionary stage and is assumed to be connected with mass-loss episodes, the appearance of macroturbulent line broadening, and the formation of clumps in the wind. Aims. To investigate a possible interplay between pulsations and mass-loss, we carried out an observational campaign of the supergiant 55 Cyg over a period of five years to search for photospheric activity and cyclic mass-loss variability in the stellar wind. Methods. We modeled the H, He i, Si ii, and Si iii lines using the nonlocal thermal equilibrium atmosphere code FASTWIND and derived the photospheric and wind parameters. In addition, we searched for variability in the intensity and radial velocity of photospheric lines and performed a moment analysis of the line profiles to derive frequencies and amplitudes of the variations. Results. The Hα line varies with time in both intensity and shape, displaying various types of profiles: P Cygni, pure emission, almost complete absence, and double or multiple peaked. The star undergoes episodes of variable mass-loss rates that change by a factor of 1.7-2 on different timescales. We also observe changes in the ionization rate of Si ii and determine a multiperiodic oscillation in the He i absorption lines, with periods ranging from a few hours to 22.5 days. Conclusions. We interpret the photospheric line variations in terms of oscillations in p-, g-, and strange modes. We suggest that these pulsations can lead to phases of enhanced mass loss. Furthermore, they can mislead the determination of the stellar rotation. We classify the star as a post-red supergiant, belonging to the group of α Cyg variables.